2016
DOI: 10.1242/jcs.186460
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Ana1 is required for centrosome assembly and centriole elongation

Abstract: Centrioles organise centrosomes and cilia, and these organelles have an important role in many cell processes. In flies, the centriole protein Ana1 is required for the assembly of functional centrosomes and cilia. It has recently been shown that Cep135 (also known as Bld10) initially recruits Ana1 to newly formed centrioles, and that Ana1 then recruits Asl (known as Cep152 in mammals) to promote the conversion of these centrioles into centrosomes. Here, we show that ana1 mutants lack detectable centrosomes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 76 publications
4
56
0
Order By: Relevance
“…It will be interesting to investigate whether Cep295 molecules on the mother centriole are rearranged and moved to the assembly site of a procentriole to trigger centriole formation. It should also be noted that while this study was under review, another studies reported that Cep295 and Ana1 regulate centriole elongation in human42 and Drosophila cells43, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…It will be interesting to investigate whether Cep295 molecules on the mother centriole are rearranged and moved to the assembly site of a procentriole to trigger centriole formation. It should also be noted that while this study was under review, another studies reported that Cep295 and Ana1 regulate centriole elongation in human42 and Drosophila cells43, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Centriole length can also be modulated by deregulation of proteins implicated in building the distal halves of centrioles, including the WD40 protein POC1 ( P roteome O f C entriole protein 1) 55 , the centrin-binding protein hPOC5 56 , or the microtubule binding protein CEP295 (Ana1 in Drosophila ) 57,58 . Interestingly, depletion of CEP295 not only impairs the recruitment of hPOC5 and POC1, but also blocks the acetylation and glutamylation of centriolar microtubules 57 .…”
Section: Centrosome Structure and Assemblymentioning
confidence: 99%
“…Best described are events in Drosophila , where PLK1 is first recruited to CPAP, through CDK1-dependent phosphorylation of a single docking site 92 . In both Drosophila and mammalian cells, PLK1 then triggers the sequential assembly of CEP135, CEP295/Ana1 and CEP152/Asl and downstream PCM formation 58,89,90 . Importantly, recruitment of Asl in Drosophila embryos only occurs after disengagement, indicating that these licensing processes occur sequentially 93 .…”
Section: Control Of Centriole Numbermentioning
confidence: 99%
“…This function depends on the Ana1 N-terminal region (Saurya et al 2016), which was reported to interact with Cep135 in the process of centriole-to-centrosome conversion in cultured cells (Fu et al 2016). Additionally, Cep135, Ana1, and Asl also affect centriole elongation in vivo evoking the question of whether or not the two pathways may be interconnected.…”
Section: Centriole Elongationmentioning
confidence: 99%